Effect of dexamethasone on TLR4 and MyD88 expression in monocytes of patients with tuberculous meningitis. (August 2017) - Zhou, Jie; Wang, Jing; Gu, Mei-Ying; Zhang, Shu-Qiong; Chen, Sheng-Li; Zhang, Xian-Wei; Zhang, Li-Na
This study aims to analyze the clinical effect of dexamethasone in the treatment of tuberculous meningitis and its effect on MyD88 and TLR4 expression in monocytes. In total, 60 tuberculous meningitis patients were divided into two groups: observation group and control group. Of them, 36 patients were treated with conventional anti-tuberculosis treatment combined with dexamethasone in the observation group, while patients in control group were treated with anti-tuberculosis alone, and the clinical efficacy and expression of TLR4 and MyD88 in peripheral blood monocytes in both the groups were analyzed. The total effective rate in the combined treatment group was 91.67%, which was significantly better than the control group (χ 2  = 5.17, P  < 0.05). This revealed that dexamethasone treatment can significantly reduce the expression levels of TLR4 and MyD88. Anti-tuberculosis treatment combined with dexamethasone can significantly improve treatment efficacy. Furthermore, the TLR4-MyD88 pathway plays an important role in the dexamethasone treatment of tuberculous meningitis.